2020
DOI: 10.1111/pin.12943
|View full text |Cite
|
Sign up to set email alerts
|

Fulminant myocarditis and pulmonary cavity lesion induced by disseminated mucormycosis in a chronic hemodialysis patient: Report of an autopsied case

Abstract: Mucormycosis is a rare fungal infection occurring in the immunocompromised host. It is difficult to diagnose, and its cardiac involvement is extremely rare. Here, we report a 64‐year‐old Japanese man with a 5‐year history of hemodialysis with disseminated mucormycosis causing fulminant myocarditis and pulmonary necrosis under glucocorticoid use. Two months before, he had received an implantable cardioverter defibrillator and started to take amiodarone for recurrent ventricular arrhythmias due to hypertensive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…using the BacT ALERT for blood culturing (17) . Another study done by Fujisawa et al in (2020) showed that hemodialysis patients are at high risk for mucormycosis due to long term of hemodialysis treatment and the use of certain medications specially in elderly (18) .…”
Section: Fungal Infection In Relation With Blood Transfusion Before O...mentioning
confidence: 99%
“…using the BacT ALERT for blood culturing (17) . Another study done by Fujisawa et al in (2020) showed that hemodialysis patients are at high risk for mucormycosis due to long term of hemodialysis treatment and the use of certain medications specially in elderly (18) .…”
Section: Fungal Infection In Relation With Blood Transfusion Before O...mentioning
confidence: 99%
“…Thus, as a precautionary measure, serial echocardiographic assessment and cardiac MRI scan is advised to post covid-19 patients after 6 weeks of presentation who had fibrosis and inflammation during the acute phase of covid [ 27 ]. Several other studies showed the possibility of Mucormycosis and Amphotericin B (causing several electrolyte imbalances) that could be the leading cause for progressive cardiac dysfunction and severe myocarditis leading to death [ 28 , 29 ].…”
Section: Risk Of Mucormycosis In Immunocompromised Patientsmentioning
confidence: 99%